Interactive Multimedia Environment Intervention with Learning Anxiety and Metacognition as Achievement Predictors - Aristea Mavrogianni; Eleni Vasilaki; Michalis Linardakis; Aikaterini Vasiou; Konstantinos Mastrothanasis (Psychology International)
Background: Interactive learning environments have emerged as transformative tools in education, enhancing engagement, academic performance, and addressing challenges like learning anxiety. This study examines the influence of multiple variables, including anxiety, internet usage for problem-solving, attitude towards a history course, metacognitive awareness, and interactive learning environments, on seventh-grade students’ academic performance. Methods: Using the Exploration of Attitudes Towards History Scale (EDIS) scale to measure attitudes and the Metacognitive Awareness of Reading Strategies Inventory-Revised Two-Factor Version (MARSI-2fR) to assess metacognitive awareness, the study evaluated historical knowledge across three stages, namely pre-intervention, post-intervention, and a one-month-later retest. A comparative analysis was conducted between the control group and the intervention group. The statistical analyses involved the calculation of correlation coefficients, the implementation of general linear models, and the performance of Wilcoxon signed-rank tests. Results: The findings indicated that prior to the intervention, factors such as learning anxiety and the extratextual component of metacognition were statistically significant predictors of achievement. However, the aforementioned factors ceased to be statistically significant when the parameter of study strategies was incorporated into the statistical model. The impact of the interactive learning environment on students’ achievement is highly statistically significant in terms of post-test scores, while the influence of all other predictors becomes insignificant. The retest confirmed the continued maintenance of the achieved results as evaluated following the intervention. Conclusions: The study confirms previous research demonstrating that interactive learning environments are an effective method of enhancing students’ academic performance and reducing the negative impact of learning anxiety.